The mind of woman - Umberger, May Ernestyne (My University, 1907)
Introduction: At the present time there is an issue which is gradually forcing itself into the minds of the people, not only of the American nation but of every civilized nation of the world. Slowly but surely it is finding expression in that great voice of the people, the literature of the day; the journals magazines and newspapers are taking in the question and such articles as, “Womans Mission”, “Womans Position in Society”, “The Worlds Half Citizens,” “The Higher Education of Woman”., appearing almost every day in some of the periodicals, all bear silent tests – mourj of the ever growing popularity of the subject and the interest that broad minded and women are exhibiting toward it. It is a question…
Citation: Umberger, May Ernestyne. The mind of woman. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Women; Women's Rights; Women's Role in the World; Theses; Manuscripts (documents)